Characteristics and Functions of the Yip1 Domain Family (YIPF), Multi-Span Transmembrane Proteins Mainly Localized to the Golgi Apparatus - Shaik, Shaheena; Pandey, Himani; Thirumalasetti, Satish Kumar; Nakamura, Nobuhiro (Frontiers in Cell and Developmental Biology, 2019)
Yip1 domain family (YIPF) proteins are multi-span, transmembrane proteins mainly localized in the Golgi apparatus. YIPF proteins have been found in virtually all eukaryotes, suggesting that they have essential function(s). Saccharomyces cerevisiae contains four YIPFs: Yip1p, Yif1p, Yip4p and Yip5p. Early analyses in S. cerevisiae indicated that Yip1p and Yif1p bind to each other and play a role in budding of transport vesicles and/or fusion of vesicles to target membranes. However, the molecular basis of their functions remains unclear. Analysis of YIPF proteins in mammalian cells has yielded significant clues about the function of these proteins. Human cells have nine family members that appear to have overlapping functions. These YIPF proteins are divided into two sub-families: YIPF/Yip1p and YIPF/Yif1p. A YIPF molecule forms a complex with a specific partner YIPF molecule. In the most broadly hypothesized scenario, a basic tetramer complex is formed from two molecules of each partner YIPF protein, and this tetramer forms a higher order oligomer. Three distinct YIPF protein complexes are formed from pairs of YIPF and YIPF proteins. These are differently localized in either the early, middle, or late compartments of the Golgi apparatus and are recycled between adjacent compartments. Because a YIPF protein is predicted to have five transmembrane segments, a YIPF tetramer complex is predicted to have 20 transmembrane segments. This high number of transmembrane segments suggests that YIPF complexes function as channels, transporters or transmembrane receptors. Here, the evidence from functional studies of YIPF proteins obtained during the last two decades is summarized and discussed.